Citizen controlled exchange of information in e-government - Gomes, H.
The online provision of public services to citizens, e-government, is here to stay. Its advantages are huge, both for the government and for the citizens. Life-event service is a sound concept in which services are designed to cater with citizen real needs instead of government departments needs. But this type of services requires interoperability between government departments. Among other things, interoperability implies the exchange of information between government departments which traditionally has been implemented by direct communication. This direct communication raises privacy concerns on citizens since their personal information is potentially exchanged without their knowledge and control. In this paper we propose an e-government model where the citizen controls the exchange of his personal information between government departments.